Does severe dietary energy restriction increase binge eating in overweight or obese individuals? A systematic review. Issue 8 (11th June 2015) - da Luz, F. Q.; Hay, P.; Gibson, A. A.; Touyz, S. W.; Swinbourne, J. M.; Roekenes, J. A.; Sainsbury, A.
Summary Severe dietary energy restriction is often used for overweight or obese individuals to achieve rapid weight loss and related health improvements. However, the extent of putative adverse effects on eating behaviour is unknown. We thus systematically searched seven databases for studies that assessed binge eating before and after severe dietary energy restriction (low or very low energy diets) in overweight or obese individuals. Fifteen clinically supervised interventions from 10 publications (nine of which involved only women) were included. Among individuals with clinically relevant pre‐treatment binge eating disorder, severe dietary energy restriction significantly decreased binge eating in all four interventions involving this population, at least during the weight loss programme. In contrast, no consistent association between severe dietary energy restriction and the onset of bingeing was found in 11 interventions involving individuals without pre‐treatment binge eating disorder, with four such interventions showing significant increases, two showing no change, and five showing significant decreases in binge eating. We conclude that clinically supervised severe dietary energy restriction appears safe and beneficial for overweight or obese individuals with pre‐treatment binge eating disorder, and does not necessarily trigger binge eating in those without binge eating disorder.